Characterization of Sulphoaluminate Cement-Asphalt Emulsion Mortar for Cement and Asphalt Mortar Repair - Yang, Chao; Li, Junhao; Zhu, Zhe; Wang, Shaohui; Liu, Yunpeng (Frontiers in Materials, 2020)
A sulphoaluminate cement-asphalt emulsion mortar was developed for the repair of damaged cement asphalt emulsion mortar. Various sulfoaluminate/Portland cement and asphalt emulsion/cement mass ratios, as well as emulsion types, were studied with respect to the setting time, rheological properties, volume stability, and mechanical properties of the repair materials in order to determine a reasonable mix proportion. The proper contents of cementitious materials and asphalt emulsion were determined. A possible relationship between the mechanical properties and the asphalt emulsion/cement mass ratio was found based on scanning electron microscopy analysis. Moreover, the shrinkage rates of the repair mortar in the fresh and hardened states showed different trends with an increase in the asphalt emulsion/cement mass ratio. The results shed light on the repair mortar for CA mortar with high efficiency and low cost.